Hubungan Pengetahuan PMIK Mengenai Pemusnahan Rekam Medis In Aktif Terhadap Efektivitas Pelayanan Rawat Inap Di Rumah Sakit X - Eka Rahmasari; Dina Sonia; Emy Wardatunisa (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: Destruction is a process of physical destruction of medical record archives that have ended their function and use value. The knowledge of medical record officers greatly influences the ongoing process of shrinking and destroying medical record files. The main problem is the problem of inpatient medical records that are too many, resulting in storage of medical records not on available shelves, which are finally stored in cardboard boxes.Methods: Data collection techniques used are observation, interviews, and questionnaires. The sampling technique used a total saturation sampling technique of 12 PMIK. Research Results: The results of the Chi square test showed that there was a significant relationship between PMIK's knowledge regarding the eradication of Inactive RMs and the effectiveness of inpatient services, with a p-value of 0.003. A p-value of less than 0.05 indicates a significant relationship between PMIK's knowledge regarding the eradication of Inactive RMs and the effectiveness of inpatient services.Conclusion: Extermination is still unscheduled and has not been carried out because there are obstacles, namely medical record officers often work with double jobs where there is no division of tasks so that the extermination has not been carried out.